What is the Competition? - Вадим Валерьевич Радаев (Journal of Economic Sociology, 2010)
Here is a short fragment of a new book that will be published in the summer 2003 with the title of: “The basics of the institutional dynamics: to the new sociology of markets”. The book will include a big theoretical part and the part devoted to empirical studies of the market that were held during the last two years.  The provided text is the theoretical part of the book. The author analyzes the notion of competition and compares several basic approaches to its definition.